Aptamer-based strategies for recognizing adenine, adenosine, ATP and related compounds. Issue 21 (10th September 2020) - Li, Yuqing; Liu, Juewen
Abstract : Adenine, adenosine, ATP and related compounds are highly important in biology. A variety of DNA and RNA aptamers have been found to selectively bind them. This article reviews important aptamers for them and their representative applications. Abstract : Adenine is a key nucleobase, adenosine is an endogenous regulator of the immune system, while adenosine triphosphate (ATP) is the energy source of many biological reactions. Selective detection of these molecules is useful for understanding biological processes, biochemical reactions and signaling. Since 1993, various aptamers have been reported to bind to adenine and its derivatives. In addition, the adenine riboswitch was later discovered. This review summarizes the efforts for the selection of RNA and DNA aptamers for adenine derivatives, and we pay particular attention to the specificity of binding. In addition, other molecular recognition strategies based on rational sequence design are also introduced. Most of the work in the field was performed on the classic DNA aptamer for adenosine and ATP reported by the Szostak group. Based on this aptamer, some representative applications such as the design of fluorescent, colorimetric and electrochemical biosensors, intracellular imaging, and ATP-responsive materials are also described. In addition, we critically review the limit of the reported aptamers and also important problems in the field, which can give future research opportunities.